The Interactions Between Local Society and Mission Hospitals in Modern China: A Case Study on Ningbo Hwa Mei Hospital (Journal for the Study of Religion and History (JSRH), 2026)
Since the First Opium War, Western medicine entered China extensively alongside missionary activities, leading to the gradual proliferation of mission hospitals across the country. Ningbo Hwa Mei Hospital 宁波华美医院 stood among the earliest of such institutions and is still of great importance. However, existing research has paid limited attention to this institution, especially in terms of the in-depth interaction between the mission hospital and local society, as well as the concrete processes of its localization—factors that are crucial for understanding how these institutions became established in China. As bearers of a heterogeneous culture, mission hospitals encountered a series of challenges in China—including social alienation, conflict, integration, and adaptation—yet they ultimately gained acceptance within local communities and achieved a degree of localization. Hwa Mei Hospital was accepted relatively early by local society, secured considerable financial support from indigenous sources, and managed to survive and develop within Ningbo’s relatively moderate political climate. However, the nursing school affiliated with Hwa Mei Hospital was regarded, amid the surge of nationalism, as an instrument of “cultural aggression” and consequently encountered opposition and resistance. At the cultural level, the hospital’s responsibility for religious propagation likewise encountered a comparable predicament. The twofold mission of the mission hospital, providing medical services and propagating religious faith, gradually grew unbalanced. The preservation of its secular functions alongside the constraints on its spiritual and cultural dimensions exemplifies both the necessary trajectory and the inevitable outcome of modern mission hospitals taking root in Chinese local societies.
Keywords: Hwa Mei Hospital, mission hospitals, modern China, Ningbo society